Dual‐functional crystalline BeO layer in enhancement‐mode ZnO/Si thin film transistors. Issue 5 (23rd February 2017) - Liang, Huili; Mei, Zengxia; Ye, Daqian; Li, Junqiang; Hong, Wen‐Chiang; Zhang, Qinghua; Liu, Yaoping; Gu, Lin; Yu, Richeng; Lu, Yicheng; Du, Xiaolong
Abstract : Integration of oxides with Si opens promising opportunities for novel multifunctional devices and new applications. To optimize the device performances through the hybrid integration, keeping the oxide/Si interface abrupt is critically important and challenging due to the seemingly unavoidable formation of amorphous SiO x or silicide interfacial layers. Here, we report an interface‐engineering approach to this issue by molecular beam epitaxy. A BeO thin layer (∼5 nm) was deposited on Si (111) surface using a two‐step process of Be deposition and oxidation. The initially formed BeO served as a template for subsequent homo‐epitaxial growth of a 10‐nm crystalline BeO layer. The well‐defined interface between BeO and Si is clearly discerned by high‐resolution transmission electron microscopy, implying the role of crystalline BeO as a barrier layer against oxygen atoms' diffusion. High‐resolution X‐ray photoelectron spectroscopy further confirmed that the combined BeO layers sufficiently protect the Si surface from oxidation. A bottom‐gate enhancement‐mode thin film transistor was established on a ZnO (130 nm)/BeO (70 nm)/Si architecture, where BeO was functionalized both as a diffusion barrier and as a high‐ k gate insulator. It indicates that this methodology can be potentially extended to hybrid integration of other technologically important crystalline oxides with Si infrastructures. Abstract : It is a challenging task to fabricate crystalline oxides on Si since Si is reactive with many elements, especially oxygen, resulting in extensive inter‐diffusion or chemical reactions. Here Liang et al. report an interface‐engineering approach to this issue by molecular beam epitaxy. A thin‐film transistor working in the enhancement mode was achieved, demonstrating it can potentially combine multi‐functional crystalline oxides with the well‐developed Si infrastructure.